Influence of personal protective equipment on the performance of life-saving interventions by emergency medical service personnel. (October 2016) - Kim, Tae Han; Kim, Chu Hyun; Shin, Sang Do; Haam, Sunnie
Prompt live-saving interventions, such as cardiopulmonary resuscitation (CPR), intravenous cannulation (IVC), and endotracheal intubation (ETI), are important for severely injured victims of chemical, biological, radiological, and nuclear (CBRN) disasters. Interventions sometime have to be performed by emergency medical service (EMS) personnel with personal protective equipment (PPE) worn in warm zones. We designed a randomized crossover simulation aimed to compare the performance of life-saving interventions in repetitive simulation of single-rescuer resuscitation wearing level-C PPE in the warm zone of a CBRN disaster. The success rate and completion time of IVC and ETI according to the presence of PPE were compared. The quality of 4-minute single-rescuer CPR was measured and compared as well. We found that the performance level of life-saving interventions performed in a simulated setting of disaster decreased when performed by EMS personnel wearing level-C PPE. Further efforts of optimizing current PPE for EMS personnel based on this study are needed.